2007
DOI: 10.1111/j.1540-8175.2006.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification by Treadmill Exercise Echocardiography in Patients with Excellent Exercise Capacity

Abstract: EE has incremental value over clinical variables, resting echocardiography, and exercise testing variables in patients with excellent exercise capacity. EE may be preferable to ECG exercise testing even in patients expected to have good exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…in these studies was good, and abnormalities measured using MPI were not predictive of cardiovascular events or outcome. 10,11 In contrast to our findings, Peteiro et al 19 reported that for men who achieved a workload of 10 or more METs and women who achieved a workload of 8 or more METs, exercise echocardiography added incremental prognostic information to clinical and exercise ECG variables when the end points of nonfatal MI and cardiac death were considered. In that study, 29% of the patients had a history of MI, 4% had an LVEF of less than 40% at rest, and 11% had an LVEF of less than 45% immediately after exercise.…”
Section: Survival (%)contrasting
confidence: 99%
See 1 more Smart Citation
“…in these studies was good, and abnormalities measured using MPI were not predictive of cardiovascular events or outcome. 10,11 In contrast to our findings, Peteiro et al 19 reported that for men who achieved a workload of 10 or more METs and women who achieved a workload of 8 or more METs, exercise echocardiography added incremental prognostic information to clinical and exercise ECG variables when the end points of nonfatal MI and cardiac death were considered. In that study, 29% of the patients had a history of MI, 4% had an LVEF of less than 40% at rest, and 11% had an LVEF of less than 45% immediately after exercise.…”
Section: Survival (%)contrasting
confidence: 99%
“…13,[16][17][18] The prognostic implications of abnormalities seen on exercise echocardiography in patients who have excellent exercise capacity have not been extensively studied. 19 The objectives of this study in patients who achieve a workload of 10 or more METs during treadmill exercise echocardiography were as follows: (1) to define the frequency of abnormal exercise echocardiographic results, (2) to identify any clinical or exercise ECG variables associated with the abnormalities seen on exercise echocardiography, (3) to ascertain all-cause and cardiovascular mortality rates, and (4) to identify any clinical or exercise echocardiographic predictors of outcome.…”
mentioning
confidence: 99%
“…3,4 Exercise echocardiography (EE) is a validated technique for the evaluation of CAD 5,6 and might overcome the limitations of exercise ECG. Although the prognostic value of EE has been demonstrated in several populations [7][8][9][10][11][12][13][14][15] only one report has evaluated its role in patients with LVH. 2 Our aim was to assess the value of treadmill EE to predict mortality and major cardiac events (MACE) in patients with LVH and confirmed or suspected CAD.…”
mentioning
confidence: 98%